Implementasi Model STAD dalam Pembelajaran PAK untuk Meningkatkan Hasil Belajar Peserta Didik di SDN 41 Sejotang - Kuslin, Thomas; Vina, Anastasia; Cenderato, Cenderato (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2024)
This research is about how effort are made to improve learning outcomes, namely by implementing the students Teams-Achievment Divisions (STAD) Model in learning. The type of research is Classroom Action Reserach. The subject in this research were Catholic Religious Education teachers and class VI students at SDN 41 Sejotang, Sanggau Regency. Observation, dokumentation and test data collection tools. Data analysis technique was qualitative descriptive. The findings in the research were: the implementation of STAD model in PAK learning has gone well. This result showed from observation during the action that the teacher had implemented learning by following each step of STAD and the students responded positively as long as this model was implemented. The improvement was known by comparing the learning results in pre-action activities, namely the result achieved were 43.75%, indicating that students have not achieved the specified classical completeness, namely 67%. After the STAD was implemented, students learning outcomes began to increase in Cycle 1 with results of 62.5%. In Cycle 2 the learning outcomes have reached the specified indicators with the result of 81.25%